Manajemen Pengelolaan UMKM Budidaya Ikan Lele Untuk Meningkatkan Pendapatan Masyarakat dalam Perspektif Maqasid Syariah - Siahaan, Rumiris; Purba, Rakhmawati; Batubara, Rizki Wulanita; Suwadi, Suwadi; Roni, Shofyan; Syahputra, Andry; Amanda, Fatia; Sihaloho, Japenton (Community Service Progress, 2024)
In running a micro, small and medium enterprise, good management elements are needed, one of which is financial management which plays a very important role in managing a business and is evidence of fund development in the modern era today. Catfish farming, which is one of the MSMEs, has become one of the main businesses of the Kuta Baru Village community, Tebing Tinggi District, Serdang Bedagai. However, there are still many catfish farmers who experience obstacles in managing their business, especially in managing their financial management. The role of the Campus through Student KKN activities tries to help solve the problems in the Kuta Baru Village community. In this activity, catfish farmers are given guidance and assistance on how to make basic financial reports such as cash flow, profit and loss, and balance sheets, as well as strategies for managing production costs, maximizing profits, and long-term financial planning. The Maqasid Syariah aspects are also applied as an effort to realize community welfare through catfish farming which has a positive impact on entrepreneurs and their families as well as the surrounding community.